Increased Mortality Rate in Rheumatoid Arthritis Patients with Neurological Symptoms or Signs Secondary to Cervical Spine Subluxations – Reduced Mortality if Postoperative Ankylosis is Achieved - Paus, Albert C.; Steen, Harald; Mowinckel, Petter; Røislien, Jo; Teigland, Jens (IntechOpen, 2012)
None